Lingual Thyroid Excision with Transoral Robotic Surgery - Elif Ersoy Callıoglu; Kazım Bozdemir; Bulent Ulusoy; Tolga Oguzhan; M. Hakan Korkmaz (Case Reports in Otolaryngology)
Ectopic thyroid gland may be detected at any place between foramen caecaum and normal thyroid localization due to inadequacy of the embryological migration of the thyroid gland. It has a prevalence varying between 1/10.000 and 1/100000 in the community. Usually follow-up without treatment is preferred except for obstructive symptoms, bleeding, and suspicion of malignity. Main symptoms are dysphagia, dysphonia, bleeding, dyspnea, and obstructive sleep apnea. In symptomatic cases, the first described method in surgical treatment is open approach since it is a region difficult to have access to. However, this approach has an increased risk of morbidity and postoperative complications. Transoral robotic surgery, which is a minimally invasive surgical procedure, has advantages such as larger three-dimensional point of view and ease of manipulation due to robotic instruments. In this report, a case at the age of 49 who presented to our clinic with obstructive symptoms increasing within the last year and was found to have lingual thyroid and underwent excision of ectopic thyroid tissue by da Vinci surgical system is presented.